Hypotension Due to Dynamic Left Ventricular Outflow Tract Obstruction after Percutaneous Coronary Intervention - Dahhan, Ali (Texas Heart Institute, 2011)
Persistent hypotension subsequent to percutaneous coronary intervention is attributed to access-site bleeding, re-infarction, or mechanical complications either of myocardial infarction or of the procedure itself (for example, pericardial tamponade). Dynamic left ventricular outflow tract obstruction after an uncomplicated percutaneous coronary intervention is an unusual, and to our knowledge not previously reported, complication that manifests itself as hypotension refractory to the usual therapy with inotropic agents. We discuss the clinical course, pathophysiology, diagnosis, and management of hypotension due to left ventricular outflow tract obstruction after percutaneous coronary intervention. Early recognition and accurate diagnosis that determines appropriate therapy will improve the patient's prospects.